PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) DIGITAL MENGGUNAKAN MACROMEDIA FLASH BERBASIS TEORI VAN HIELE PADA PEMBELAJARAN MATEMATIKA DISMP NEGERI 1 TEMPUNAK - Indry Anggraeni Arahim; Dede Suratman; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this study is to find out the validity of digitalworksheetsdeveloped withmacromedia flash based on Van Hiele theory on cube material and to know thestudent's learning results after using the digital worksheets. The research wasconducted at SMP Negeri 01 Tempunak in the even semester. The subjects of the studywere 12 grade VIII students. The type of research used are Research and Developmentresearch using ADDI (analysis, design, development, and implementation) model.Researchers measured the level of effectiveness of this study with a minimum learningmastery standard (KKM) that is 70. The validity of digital worksheets can be seen frommedia experts, learning materials experts and alumi experts master of mathematicseducation UNTAN leads to the same decision that is the feasibility of the product thathas been produced to be used as a medium in mathematics learning. Based on thestudent's study results, it was obtained that 10 students completed while 2 students hadnot reached KKM. After being converted with a scale conversion table from the studyresults 12 students presentase 83.33% achievement level is in good qualifications.Keywords: Digital Worksheet, Macromedia Flash, Van Hiele Theory